E-Government in marketing a country: A strategy for reducing transaction cost of doing business in Tanzania - Kachwamba, Muhajir; Sæbø, Øystein (International Journal of Marketing Studies, 2024)
A research paper submitted to the International Journal of Marketing Studies Vol. 3, No. 4; November 2011